Fatty acid profile and storage stability of loin muscle in response to dietary supplementation of Spirulina platensis in finishing crossbred pigs - Lakshmi, M; Ravi, A; Devasena, B; Shakeela, S; Reddy, G V Bhaskara (Journal of Meat Science, 2024)
The study was conducted to study whether feeding Spirulina platensis has beneficial effect on enhancing the fatty acid profile and storage stability of the loin muscle of pigs. A total of 24 male finishing pigs (Large White Yorkshire X Desi) were housed individually and distributed randomly into four equal groups with six animals in each group. Four isonitrogenous experimental diets (T1 to T4) were formulated by including dry Spirulina platensis at 0, 0.5, 1.0 and 1.5 %, respectively and fed during finishing phase (50 to 75 kg) live weight. Dietary treatments had no significant (P>0.05) effect on the total lipid and total cholesterol content of the loin muscle of pigs. The level of polyunsaturated fatty acids (PUFA) was higher (P<0.05) in Spirulina supplemented groups (T2, T3, and T4) compared to T1 leading to a higher (P<0.05) ratio of PUFA to saturated fatty acid (SFA) with increasing levels of Spirulina platensis inclusion in the diet. Whereas, the sum of SFA and monounsaturated fatty acids (MUFAs) was significantly (P<0.05) decreased in Spirulina supplemented groups compared to T1. The Ratio of n-6 to n-3 of muscle was decreased significantly (P<0.05) with increasing level of Spirulina and the values were 21.5, 20.2, 20.1, and 19.8 in T1 to T4, respectively. The other fatty acids namely gamma-linolenic acid, alpha-linolenic acid and eicosapentanoic acid were not statistically significant (P>0.05) among the treatment groups. Supplementation of Spirulina significantly (P<0.05) decreased the pH and 2-TBARS value of loin muscle during the refrigerated (4±1°C) storage at 0, 3, 6, and 9 days. Further, inclusion of Spirulina showed significant (P<0.05) improvement in the sensory attributes (flavour, tenderness, and juiciness) of the loin muscle of pigs. The results indicated that inclusion of dried Spirulina platensis powder up to 1.5 % in finishing pig diets was beneficial to achieve PUFA enriched pork and overall acceptability of the pork during refrigerated storage for a period of 9 days.